Health related quality of life, anxiety and depression among tuberculosis patients in Kathmandu. - Devkota,Janardan (2013)
ABSTRACT: The objective of this study was to assess the HRQoL anxiety and depression level of TB patients. Sample size was 150 questinnaires containing socio-demographic characterstics, SRQ-20, SF-36v2, HAM-A, and HAM-D. SRQ-20 for rule out psychiatric comorbidity, SF-36v3 for nine domain of HRQoL generic tool calculating and scoring. HAM-A and HAM-D for rating anxiety and depression diagnosed by SRQ-20 scoring and calculating. Epi-info7, SPSS 20, and SF-36 Scoring Software were use data management and analysis. Majority (57.3%) were male belonging to 21-25 years age group and mean age 29.10. 63% of respondents are not the permanent resident of Kathmandu. 58.9% respondents had educational status higher tha grade 10 or higher. 51.3% respondents aare suffered from EPTB where gland TB was higer prevalence. Very few respondents were rating clinical attention needed anxiety and depression. 90.6% respondents had mot any other co-morbidity of disease. Over all HRQoL was found poor only 1.4% female and 1.7% males HRQoL was above the average. All other HRQoL was below average. All respondents in ths study were diagnose psychotic comorbidity. Similarly HRQoL shows MCS score in below average in majority of respondents. In the PTB patients there was no correlation between anxiety, depression, MCS and PCS score but in EPTB patients there was strong correlation between depression and anxiety. Poor negative significant correlation between MCS and PCS score. There was no association between gender and PCS score on both types TB patients. As same results found in gender and MCS patients. The findings of this study can be used as baseline data to further rule out the HRQoL, anxiety and depression in TB patients in Nepal.